Convergence of Infinite Product by Schlömilch's Method - Kumar, Nand Kishor (Tribhuvan University Journal, 2023)
This paper presents the resolution of sine and cosine as an infinite product from Schlomilch method. It also discusses the convergence of the infinite products of sin θ and cos θ. Some important Series from Infinite Product has been evaluated.